2022
DOI: 10.1111/mec.16339
|View full text |Cite
|
Sign up to set email alerts
|

Long‐distance migration is a major factor driving local adaptation at continental scale in Coho salmon

Abstract: Inferring the genomic basis of local adaptation is a long-standing goal of evolutionary biology. Beyond its fundamental evolutionary implications, such knowledge can guide conservation decisions for populations of conservation and management concern. Here, we investigated the genomic basis of local adaptation in the Coho salmon (Oncorhynchus kisutch) across its entire North American range. We hypothesized that extensive spatial variation in environmental conditions and the species' homing behaviour may promote… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 136 publications
5
44
0
Order By: Relevance
“…Here, we observed a distinct genetic split between the Thompson populations and all other populations, a pattern which is consistent with previous studies using SNP markers (Beacham et al, 2020), microsatellite and MHC markers (Beacham et al, 2001;, and mitochondrial DNA haplotypes (Smith et al, 2001). Furthermore, Rougemont et al (2022) identified evidence for local adaptation to conditions related to The definition of CUs for Pacific salmon was an important first step in the implementation of the WSP in Canada (DFO, 2005). The intent of these units was to represent biologically meaningful entities of diversity for standardized monitoring of the status of all five wild salmon species and assessing impacts of actions taken to conserve and manage wild populations (DFO, 2009).…”
Section: Broad Scale Patterns Of Genetic Structuresupporting
confidence: 90%
See 2 more Smart Citations
“…Here, we observed a distinct genetic split between the Thompson populations and all other populations, a pattern which is consistent with previous studies using SNP markers (Beacham et al, 2020), microsatellite and MHC markers (Beacham et al, 2001;, and mitochondrial DNA haplotypes (Smith et al, 2001). Furthermore, Rougemont et al (2022) identified evidence for local adaptation to conditions related to The definition of CUs for Pacific salmon was an important first step in the implementation of the WSP in Canada (DFO, 2005). The intent of these units was to represent biologically meaningful entities of diversity for standardized monitoring of the status of all five wild salmon species and assessing impacts of actions taken to conserve and manage wild populations (DFO, 2009).…”
Section: Broad Scale Patterns Of Genetic Structuresupporting
confidence: 90%
“…Previous studies identified a strong signal of latitudinal isolation by distance (IBD) across the entire North American distribution of Coho salmon due to the northward postglacial population expansion (Rougemont et al, 2020(Rougemont et al, , 2022. Similarly, we evaluated the relationship between genetic diversity (H s ) and genetic differentiation (β ST ) and the distance from the southernmost site to assess the potential confounding effect of latitude on subsequent genotypeenvironment association (GEA) analyses.…”
Section: Population Genetic Structurementioning
confidence: 99%
See 1 more Smart Citation
“…These declines have prompted intense interest in understanding the genetic basis of ecologically important traits as well as the development of genome editing technology to aid in conservation efforts (Phelps, Seeb, & Seeb, 2020;Waples, Naish, & Primmer, 2020). However, the variation of gene copy number produced by differential rediploidization between species and inconsistent gene naming complicates these efforts (Limborg, Larson, Seeb, & Seeb, 2017;Rougemont et al, 2022) mykiss gardeneri) (Chen, Farrell, Matala, & Narum, 2018). Through our investigation we produced a gene family-based homology guide for Oncoryhynchus which includes both gene name (NCBI ID) and copy number that we hope we will serve as an easy to use resource for the salmonid community to address the issue of homolog identification.…”
Section: Introductionmentioning
confidence: 99%
“…These declines have prompted intense interest in understanding the genetic basis of ecologically important traits as well as the development of genome editing technology to aid in conservation efforts (Phelps, Seeb, & Seeb, 2020; Waples, Naish, & Primmer, 2020). However, the variation of gene copy number produced by differential rediploidization between species and inconsistent gene naming complicates these efforts (Limborg, Larson, Seeb, & Seeb, 2017; Rougemont et al, 2022) by making the identification of homologous genes, a prerequisite for either genetic analysis or genome editing efforts extremely challenging.…”
Section: Introductionmentioning
confidence: 99%